Manajemen Risiko Kecelakaan Kerja Berdasarkan OHSAS 18001:2007 di Subdep Perkakas PT Pindad (Persero) – Divisi Munisi - Lindawati Hermawan; Sahala Manalu; Daniel Prasetyo (JURNAL ILMU MANAJEMEN, 2014)
Every manufacturing company faces safety risks in its production process. OHSAS 18001:2007 certification is required by international companies for ensuring that they have good safety and health management. The purpose of this research is to identify, assess, and define mitigation for safety risk in PT Pindad (Persero) – Munition Division’s Appliance Sub-Department based on OHSAS 18001:2007. The result shows that the safety risk factors in Appliance Sub-Departments are electricity shock, tools graze, tools cut, sprained limb, tools crush, dust and grindstone fragments, and cutting oil burst. Those risks happen because of human behavior, infrastructure, and working tool factors as shown in fishbone diagram. Most safety risks are included in low risk category and can be handled through administrative controls and personal protective equipment (PPE) usage. Some safety risks are included in medium risk category and need to be handled through engineering control and PPE usage.